Pasang dan Kepemimpinan Ammatoa: Memahami Kembali Sistem Kepemimpinan Tradisional Masyarakat Adat dalam Pengelolaan Sumberdaya Hutan di Kajang Sulawesi Selatan - Pawennari Hijjang (Antropologi Indonesia, 2005)
This article analyses forest resources management in Tana Toa, South Sulawesi, headed by Ammatoa. Keammatoan membership is divided into Ilalang embaya or adat area and Ipantaran gembaya or outside adat area. The adat allows possibility of empowering local institutions to manage forest resources in the context of regional autonomy. This paper discusses to what extent Ammatoa leadership and adat have been used for managing forest resources through reflective mutual understanding process which lead to the transformation to an open community. Key words: 'pasang'; 'ammatoa'; 'kamase-masea'; traditional leadership.